SARS-CoV-2 modulates inflammatory responses of alveolar epithelial type II cells via PI3K/AKT pathway - Al-Qahtani, Ahmed A.; Pantazi, Ioanna; Alhamlan, Fatimah S.; Alothaid, Hani; Matou-Nasri, Sabine; Sourvinos, George; Vergadi, Eleni; Tsatsanis, Christos (Frontiers in Immunology, 2022)
Background: SARS-CoV-2 infects through the respiratory route and triggers inflammatory response by affecting multiple cell types including type II alveolar epithelial cells. SARS-CoV-2 triggers signals via its Spike (S) protein, which have been shown to participate in the pathogenesis of COVID19. Aim: Aim of the present study was to investigate the effect of SARS-CoV2 on type II alveolar epithelial cells, focusing on signals initiated by its S protein and their impact on the expression of inflammatory mediators. Results: For this purpose A549 alveolar type II epithelial cells were exposed to SARS CoV2 S recombinant protein and the expression of inflammatory mediators was measured. The results showed that SARS-CoV-2 S protein decreased the expression and secretion of IL8, IL6 and TNFα, 6 hours following stimulation, while it had no effect on IFNα, CXCL5 and PAI-1 expression. We further examined whether SARS-CoV-2 S protein, when combined with TLR2 signals, which are also triggered by SARS-CoV2 and its envelope protein, exerts a different effect in type II alveolar epithelial cells. Simultaneous treatment of A549 cells with SARS-CoV-2 S protein and the TLR2 ligand PAM3csk4 decreased secretion of IL8, IL6 and TNFα, while it significantly increased IFNα, CXCL5 and PAI-1 mRNA expression. To investigate the molecular pathway through which SARS-CoV-2 S protein exerted this immunomodulatory action in alveolar epithelial cells, we measured the induction of MAPK/ERK and PI3K/AKT pathways and found that SARS-CoV-2 S protein induced the activation of the serine threonine kinase AKT. Treatment with the Akt inhibitor MK-2206, abolished the inhibitory effect of SARS-CoV-2 S protein on IL8, IL6 and TNFα expression, suggesting that SARS-CoV-2 S protein mediated its action via AKT kinases. Conclusion: The findings of our study, showed that SARS-CoV-2 S protein suppressed inflammatory responses in alveolar epithelial type II cells at early stages of infection through activation of the PI3K/AKT pathway. Thus, our results suggest that at early stages SARS-CoV-2 S protein signals inhibit immune responses to the virus allowing it to propagate the infection while in combination with TLR2 signals enhances PAI-1 expression, potentially affecting the local coagulation cascade.